Bridging the gap: evaluating Indonesia’s national income and societal welfare through an Islamic economic perspective - Aslamiyah, Saibatul (Journal of Islamic Economics Management and Business (JIEMB), 2024)
National income is a critical indicator of a country’s economic health, reflecting its capacity to generate income and distribute wealth. This study focuses on Indonesia, the largest economy in ASEAN, whose Gross National Income (GNI) ranks first in the region, yet its GDP per capita remains comparatively low. The study aims to assess how well Indonesia’s national income translates into societal welfare, emphasizing income inequality. Using national data from credible sources such as the World Bank and Indonesian Statistics Bureau, the research employs a macroeconomic framework and Keynesian consumption model to evaluate the distribution of wealth. The findings reveal a substantial gap between Indonesia’s high national income and its uneven income distribution, evidenced by a rising Gini Index. The research explores Islamic economic principles, particularly the concept of maqāṣid sharīah, to propose a fairer income distribution model that could enhance societal welfare. The study’s implications suggest that incorporating Islamic fiscal tools such as zakat could bridge economic disparities, fostering equitable and sustainable development in Indonesia.